Analysis of landscape structure of the Braço River sub-basin as subsidy for a project of Payment for Ecosystem Services in the city of Camboriu, Santa Catarina, Brazi - Antunes, Pedro Paulo; Carvalho, Rosemeri Marenzi; Espinoza, Helia Del Carmen Farias (Sociedade & Natureza, 2017)
Landscape Ecology has become an important tool for decision-making in the planning of land use. Theaim of this study was to analyze land use and land cover of the Braço River hydrographic sub-basin, assupport for the Projeto Produtor de Água (Water Producer Project). This initiative is being introduced inthe municipality of Camboriú, in the State of Santa Catarina for PSA (Payment for Ecosystem Services).Geoprocessing Technologies were used, namely: satellite imaging (Quickbird) and Geographic InformationSystems (Spring 5.2.4 and ArcGis 10). The analysis of land use and land cover indicates a prevalenceof Medium and Advanced Stage Forest (74.04% of the sub-basin). Between elements of the landscape,the patch Medium and Advanced Stage Forest was the most significant, and is therefore the landscapematrix. However, connectivity may be prejudiced by fragmentation, due to the lack of corridors in thePermanent Protect Areas (APPs) along the margins of water courses, and the presence of the highwaysystem as barriers. This methodology enables to obtained a profile of the landscape and detect the needfor planning of this use, based on principles of Landscape Ecology, with a focus on connectivity of landfragments.